[PP.07.08] METABOLOMIC STUDY OF PATHWAYS UNDERLYING HEXADECANEDIOATE INDUCED BLOOD PRESSURE ELEVATION. (September 2016) - Alharbi, N.; McBride, M.W.; Graham, D.; Padmanabhan, S.
Abstract : Objective: A putative novel pathway for blood pressure regulation involving the dicarboxylic acid hexadecanedioate was identified in a study associating blood pressure and mortality outcomes with fasting blood metabolites. The functional role of hexadecanedioate on blood pressure elevation and vascular reactivity was confirmed by oral administration of hexadecanedioic acid to Wistar Kyoto (WKY) rats. This study aimed to characterize the metabolic effects of hexadecanedioic acid administration in WKY rats to identify metabolic pathways underlying hexadecanedioate-induced blood pressure elevation. Design and method: Eleven-week-old male WKY were treated orally with hexadecanedioic acid (250 mg/kg per day; n = 5) or vehicle (n = 5) for 3 weeks. At sacrifice tissues (aorta, heart, brain, adipose, kidney, and liver) were harvested and global metabolic profiles analysed by UPLC-MS/MS (Metabolon). Data was analysed using random forest classification and the top rank metabolites were highlighted for further investigation. Results: Treatment with hexadecanedioic acid increased hexadecanedioate levels in all tissues tested except the brain, potentially reflecting poor diffusion through the blood-brain barrier. Random Forest (RF) classification of metabolites gave a predictive accuracy of 80% for heart and 100% for kidney. The RF Importance Plot of the 30 top-ranking metabolites indicates key differences in lipid, carbohydrate and amino acid metabolism. In heart, increased fatty acids (e.g. acylcarnitines, complex lipids, and lysolipids) in treated rats suggest impairment of fatty acid beta-oxidation. Heart also demonstrated elevated levels of glycogen breakdown products indicating increased glucose demand. In contrast, kidneys demonstrated an increase in long-chain fatty acids and ketone body beta-hydroxybutyric acid, and a decrease in maloylcarnitine suggesting increased beta-oxidative use. In adipose tissue dicarboxylate fatty acids (tetradecanedioate and octadecanedioate) were elevated suggesting hexadecandioic acid caused a decrease in beta-oxidation and a shift towards use of peroxisomal omega-oxidation. In liver, hexadecanedioic acid increased cysteine-glutathione disulfide levels suggesting an enhanced oxidising environment. Conclusions: Exogenous administration of hexadecanedioic acid in addition to increasing blood pressure impacts a number of metabolic readouts including changes related to lipid and glucose metabolism and redox homeostasis. These pathways are putative targets for further research to elucidate the mechanism by which hexadecanedioate affects blood pressure.